2011
DOI: 10.1126/scisignal.2001754
|View full text |Cite
|
Sign up to set email alerts
|

AKT Promotes rRNA Synthesis and Cooperates with c-MYC to Stimulate Ribosome Biogenesis in Cancer

Abstract: Precise regulation of ribosome biogenesis is fundamental to maintain normal cell growth and proliferation, and accelerated ribosome biogenesis is associated with malignant transformation. Here, we show that the kinase AKT regulates ribosome biogenesis at multiple levels to promote ribosomal RNA (rRNA) synthesis. Transcription elongation by RNA polymerase I, which synthesizes rRNA, required continuous AKT-dependent signaling, an effect independent of AKT's role in activating the translation-promoting complex mT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
134
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(145 citation statements)
references
References 68 publications
7
134
2
2
Order By: Relevance
“…The stimulatory effect of activated Akt on rRNA synthesis was, until recently, thought to be mediated by the mammalian target of rapamycin (mTOR). However, recent data have demonstrated that inhibition of mTOR activity by rapamycin has little effect on rRNA synthesis, although sustained inhibition of both Akt and mTOR markedly suppress both rRNA synthesis and ribosome biogenesis by limiting RNA polymerase I (Pol I) loading onto DNA and by reducing pre-rRNA processing (3). These observations support the view that Akt may play a critical role in controlling ribosomal biogenesis, but the mechanism by which it does so has not been defined.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…The stimulatory effect of activated Akt on rRNA synthesis was, until recently, thought to be mediated by the mammalian target of rapamycin (mTOR). However, recent data have demonstrated that inhibition of mTOR activity by rapamycin has little effect on rRNA synthesis, although sustained inhibition of both Akt and mTOR markedly suppress both rRNA synthesis and ribosome biogenesis by limiting RNA polymerase I (Pol I) loading onto DNA and by reducing pre-rRNA processing (3). These observations support the view that Akt may play a critical role in controlling ribosomal biogenesis, but the mechanism by which it does so has not been defined.…”
supporting
confidence: 72%
“…Although cellular transformation has been most frequently related to the dysregulation of protein translation as a consequence of mTOR activation (35,36), the role of Akt in enhancing ribosomal biogenesis is receiving increasing attention (3,37). The up-regulation of rRNA synthesis is a prerequisite for all tumors and presents a unique opportunity for therapeutic intervention (38).…”
Section: Discussionmentioning
confidence: 99%
“…For example, increased rRNA transcription and ribosomal biogenesis were observed in cancers subject to c-Myc activation (17,18). To this end, we therefore examined the protein concentrations and cell proliferation in MDA-MB-231 cells with HSPC111/RTCD1 knockdown.…”
Section: Attenuated Protein Synthesis Upon Hspc111 and Rtcd1 Reductionmentioning
confidence: 99%
“…Enhanced rRNA synthesis and ribosomal biogenesis are commonly seen in human cancers coupled with resultant protein translation and cell-proliferation acceleration (17)(18)(19). The effect of c-Myc on driving cell growth is in part due to its role in transcribing rDNA and advancing ribosomal biogenesis (20).…”
Section: Introductionmentioning
confidence: 99%
“…The PI3K-AKT-mTOR and RAS pathways cooperate with MYC to control ribosome biogenesis and protein synthesis in normal and malignant cells (20,21), with the PI3K-AKTmTOR pathway in particular regulating ribosome biogenesis and function at multiple steps. PI3K-AKT-mTOR signaling controls rRNA synthesis at the levels of rDNA transcription and rRNA processing as well as RP synthesis by regulating translation initiation for 5′ terminal oligopyrimidine (TOP)-containing mRNAs (20,(22)(23)(24). PI3K-AKT-mTOR signaling modulates mRNA translation at both the initiation and elongation stages, including the promotion of eIF4E-dependent 5′ CAP-dependent translation initiation (20,21,23,25,26).…”
Section: Research Briefmentioning
confidence: 99%